Assessing Initial Psychometric Properties of the Armenian Version of the Miller Forensic Assessment of Symptoms Test (M-FAST) with Psychiatric Patients and Simulator Participants. Issue 4 (8th August 2021) - Ter-Stepanyan, Anahit; Azizian, Allen; Gasparyan, Khachatur; Ghazaryan, Gayane; English, Peter
ABSTRACT: Psychological tests to detect malingered or feigned symptoms of mental illness are critical in the assessment of forensic patients. The Miller Forensic Assessment of Symptoms Test (M-FAST) is a validated screening test for identifying malingered mental illness. The objective of this study was to translate, adapt, and validate the M-FAST into Armenian. Fifty-four psychiatric patients and 54 simulator participants drawn from the Republic of Armenia were tested with an M-FAST that had been translated into Armenian. The Armenian M-Fast Total and Subscale scores were comparable to the original version with adequate-to-high internal consistency. M-FAST total scores were significantly higher in the simulator group ( M = 12.83) than psychiatric patients ( M = 6.83) [ d = 1.46]. Results provide evidence that the Armenian translation of the M-FAST is comprehensible to both test-taker and test-administrator and represents a promising screening measure for the detection of feigned symptoms of mental illness.